Introducing human rights and health into a nursing curriculum - P. Mayers (AOSIS, 2007)
An important component of nursing programmes in South Africa has been teaching of the principles of ethical practice and relevant ethical codes. A number of factors have contributed to the need to include human rights as an integral component of nursing curricula in South Africa. These include the Bill of Rights in the Constitution of South Africa and the implications thereof for health care delivery, the primary health care approach in the delivery of health care in South Africa, the development and acceptance o f Patients' Rights Charters, and the recognition of the role that health professionals played - whether through lack of knowledge and awareness or direct involvement - in the human rights violations in the health sector exposed during the hearings of the Truth and Reconciliation Commission.